Parental perceptions of COVID-19–like illness in their children. (May 2021) - Hodson, A.; Woodland, L.; Smith, L.E.; Rubin, G.J.
Abstract: Objectives: The objective of the study is to explore parents' perceptions of COVID-19–like symptoms in their child and attitudes towards isolating from others in the household when unwell. Study design: The study used qualitative, semistructured interviews. Methods: The study involved thirty semistructured telephone interviews with parents of children between 4 and 18 years. Thirty semistructured telephone interviews with parents of children between 4 and 18 years. Results: We found four themes relating to symptom attribution ('normalising symptoms', 'err on the side of caution', 'experience of temperature', 'symptoms not normal for us'). In general, parents were more likely to attribute symptoms to COVID-19 if a temperature was present or the symptoms were perceived as 'unusual' for their family. Four themes relating to self-isolation ('difficult to prevent contact with children', 'isolation would be no different to lockdown life', 'ability to get food and supplies', 'limited space'). Parents believed they would find isolation within the household difficult or impossible if they had dependent children, had limited space or could not shop for groceries. Conclusions: The findings highlight complexities in symptom perception, attribution and household isolation. We suggest that they can be overcome by (a) providing better guidance on what symptoms require action, (b) providing guidance as to how to prevent infection within the household and (c) by supporting families with grocery shopping through a potential second or third wave.